An Interesting Case of a Large Cystic Mesothelioma of the Omentum in a Pediatric Patient - Gnanasekar Periyasamy; Sivasundhar Kumarasamy; Karumuri Srinivas Sekhar; Malathi Vaithyanathan; Saravanakumar Sengottaiyan; Saravanan Thangam Shanmugasundaram; Kumaragurubaran Gnanasambandam (Thieme Medical and Scientific Publishers Pvt. Ltd., 2019)
We present an interesting case of a large intra-abdominal cystic lesion in a 14-year-old girl who presented with abdominal discomfort and pain. The patient was evaluated with magnetic resonance imaging (MRI) and found to have a large septated cystic lesion arising from the gastrohepatic omentum. She underwent surgery, and the diagnosis of cystic mesothelioma was confirmed in the histopathology. To the best of our knowledge, only a few cases of benign omental mesothelial cysts have been reported.